Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/3883822
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transcriptomic Signatures between Monkeypox-Infected Monkey and Human Cell Lines

Abstract: Monkeypox virus (MPV) is a smallpox-like virus belonging to the genus Orthopoxvirus of the family Poxviridae. Unlike smallpox with no animal reservoir identified and patients suffering from milder symptoms with less mortality, several animals were confirmed to serve as natural hosts of MPV. The reemergence of a recently reported monkeypox epidemic outbreak in nonendemic countries has raised concerns about a global outburst. Since the underlying mechanism of animal-to-human transmission remains largely unknown,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 78 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…They also compared the expression profile of MPXV to VACV and found that only the minority of transcripts are species-specific 15 . And though recent studies have re-evaluated these data using comparative pathway analyses, the detailed transcriptomic characteristics of MPXV-infected cells remains undescribed 16 . Thus, while micro-array-based techniques reveal useful insights, they are unable to resolve many aspects of the transcriptome, including the detection of the plethora of different transcript isoforms, which have been detected in closely related viruses, for example in VACV 17 .…”
Section: Background and Summarymentioning
confidence: 99%
“…They also compared the expression profile of MPXV to VACV and found that only the minority of transcripts are species-specific 15 . And though recent studies have re-evaluated these data using comparative pathway analyses, the detailed transcriptomic characteristics of MPXV-infected cells remains undescribed 16 . Thus, while micro-array-based techniques reveal useful insights, they are unable to resolve many aspects of the transcriptome, including the detection of the plethora of different transcript isoforms, which have been detected in closely related viruses, for example in VACV 17 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Next, we used the median expression of targeted genes and then performed a differential analysis with an algorithm in the "DESeq2" package in R/Bioconductor. After the differential analysis, results were utilized for the gene set enrichment analysis (GSEA) with the Hallmark database [71][72][73]. Then, we used the "fgsea" packages in R Studio software to evaluate enriched pathways in transcriptional data by the GSEA, and online platform (http://www.bioinformatics.com.cn/) and used "SRplot" for visualization (http://www.bioinformatics.com.cn/ srplot) [74,75].…”
Section: Functional Enrichment and Mirna-regulated Network Analysesmentioning
confidence: 99%
“…While millions of deaths were reported worldwide due to the SARS-CoV-2 pandemic [ 1 ], a new zoonotic disease, monkeypox (mPox), caused by the monkeypox virus (MPV), has become a severe public health concern. The monkeypox virus, closely related to the variola virus that causes smallpox, was initially identified in monkeys in 1958 [ 2 ] and in humans in a forested area of central Africa in 1970 [ 3 , 4 ]. While mPox is endemic in parts of west and central Africa, its recent occurrence in a number of nonendemic locations outside of Africa has caused public health officials to express grave concerns [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While mPox is endemic in parts of west and central Africa, its recent occurrence in a number of nonendemic locations outside of Africa has caused public health officials to express grave concerns [ 5 ]. Since smallpox was eradicated due to widespread vaccination, there have been very few natural outbreaks of the Orthopoxvirus until recently [ 2 ]. However, after the confirmed outbreaks in over 70 countries where the virus has not been reported before, the World Health Organization on July 23 issued its highest level alert, designating mPox as a public health emergency of international concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation